Acid Leaching of Uranium from Weathered Uraniferous Black Shale - Tariq M Bhatti (International Journal of Economic and Environment Geology)
This paper describes the chemical leaching of uranium from weathered black shale by using sulfuric acid (H2SO4) andacidic ferric sulfate (Fe2(SO4)3solutions as lixiviants. The black shale sample was radioactive in nature due to the presence of uranium and its decay radio-isotope products like 226Ra, 214Pb and 214Bi. The γ-activity of natural 235U was 97.6 ± 1.34 Bq Kg-1. The shale sample showed 48±1% porosity with bulk density of 1.38 ± 0.015 g/ cm3. The main minerals identified in the weathered shale sample were quartz, illite, microcline (K-feldspar), anorthite(Ca-feldspar), gypsum and hematite. A mixed layer illite-smectite phase at 10.8Å was also detected indicating the weathering of clay minerals present in the shale sample. The shale sample was polymetallic in nature and contained 0.005% U3O8, 0.24% V2O5, 0.038% NiO, 0.012% CuO, 0.037% CeO2and 0.019% ZnO on dry matter basis. The shale sample was organic carbon rich and contained 19.60% C, 1.25% N and 2.50% H, which indicated the presence of nitrogenous hydrocarbon compound(s). Uranium was present in the tetravalent oxidation state (U4+) in the shale matrix.A series of leaching experiments were conducted in shake flasks and percolation column for uranium dissolution from black shale with and without acidic ferric sulfate solutions of pH 1.5 and pH 2.0 at 30±2 °C. Uranium leaching efficiency was mainly attributed to the concentrations of H2SO4and Fe3+ ions in the leaching solutions. Uranium dissolution from the weathered black shale mainly attributed to redox reaction of U4+to U6+with Fe3+as an oxidant in acidic leaching environment